“Whiteness” and the Gendered Space: The Case of Hester Prynne in Hawthorne’s The Scarlet Letter - Ayan Mondal (PostScriptum: An Interdisciplinary Journal of Literary Studies, 2022)
Hawthorne’s The Scarlet Letter one of the iconic romances in American fiction which has been heralded as a pioneering text foregrounding early American fears, inhibitions, conventions, social practices, and religious order. Thematically, the novel lends itself to universalist dimensions as well where, apparently, immediate social problems like that of slavery and Red-Indian intrusions do not come to the fore. The character of Hester Prynne is also one of the baffling intrusions into the so-called status of a stigmatised woman who transforms herself from the state of being “adulterous” to one of becoming “able”. The aim of the present article is, however, not to present another picture of her fallen and hapless status in society which earlier criticisms have abundantly ventured into. The aim of the present article is rather to talk about her essential “blackness” as an “other-mother” and the textual politics that treats her in an apologetic light. The article takes into account the key generalizations of Toni Morrison forwarded in her book Playing in the Dark: Whiteness and the Literary Imagination, particularly in the chapter “Romancing the Shadow”. This article tries to show how Hawthorne very conveniently romances on the “black” shadow in the text and crafts his characterization of Hester accordingly. Therefore, the article would try to reveal the gendered space lying submerged in the text by using the principles of racial dynamics offered by Morrison’s take on whiteness and the play of “literary imagination” to fictionally represent it.